A Comprehensive Lighting Configuration for Efficient Indoor Visible Light Communication Networks - Thai-Chien Bui; Suwit Kiravittaya; Keattisak Sripimanwat; Nam-Hoang Nguyen (International Journal of Optics)
Design of an efficient indoor visible light communication (VLC) system requires careful considerations on both illumination and communication aspects. Besides fundamental factors such as received power and signal-to-noise ratio (SNR) level, studies on mobility scenarios and link switching process must be done in order to achieve good communication link quality in such systems. In this paper, a comprehensive lighting configuration for efficient indoor VLC systems for supporting mobility and link switching with constraint on illumination, received power, and SNR is proposed. Full connectivity in mobility scenarios is required to make the system more practical. However, different from other literatures, our work highlights the significance of recognizing the main influences of field of view angle on the connectivity performance in the practical indoor scenarios. A flexible link switching initiation algorithm based on the consideration of relative received power with adaptive hysteresis margin is demonstrated. In this regard, we investigate the effect of the overlap area between two light sources with respect to the point view of the receiver on the link switching performance. The simulation results show that an indoor VLC system with sufficient illumination level and high communication link quality as well as full mobility and support link switching can be achieved using our approach.